The peer tutoring programme as an effective learning enhancement strategy - Md. Noor, Nor Azian; Othman, Joharry (International Islamic University Malaysia (IIUM), 2011)
This paper reports on the Peer Tutoring Programme conducted by the Student Learning Enhancement Unit (SLEU) at the Gombak Campus of the International Islamic University Malaysia. The programme was first launched in July 2004. The report is based on data available for three regular academic semesters, semester 1, 2007-2008, semester 2, 2007-2008)and semester 1, 2008-2009). It provides information on the participants’ profiles and their progress in terms of changes in their academic achievement (CGPA) and includes some recommendations for further improvement of the programme. SLEU finds the programme successful and it offers many benefits to the tutees as well as tutors. The IIUM experience should be a showcase for other institutions of higher learning, to examine and perhaps implement, as a means of enhancing and sustaining student academic achievement.